Inovasi Sociopreneur : Transformasi Sampah Menjadi Produk Ekonomis Berkelanjutan pada Bank Sampah Anggrek, Kelurahan Bendogerit, Kota Blitar - Ulva Roifatul Lailin; Wydha Mustika Maharani; Yusada Andri Hermawan (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
This Community Service Programme was implemented to address the issues faced by Bank Sampah Anggrek's partners in Bendogerit Village, Blitar City. The main problems faced by the partners included limited variety of recycled products, simple waste processing techniques, and ineffective marketing strategies. Activities include socialisation, strengthening local partnerships, recycling training, and digital marketing assistance. As a result, members of the Waste Bank were able to create three new products: plant pots made from orange peels, carnival costumes made from fabric and plastic waste, and ecobrick furniture, and establish collaborations with two local businesses. The constraints of the Community Service Programme activities included limited production facilities, inconsistent participant attendance, low digital literacy, and competition with traditional waste collectors. This programme demonstrates that a waste bank-based sociopreneurship model can have economic, social, and environmental impacts while supporting sustainable waste management strategies. The programme was also successful due to its participatory approach, which actively involved Anggrek Waste Bank members in every step. Participants not only gained new information, but also acquired practical skills that can be used in the processing and marketing of recycled goods. This community service programme greatly helps to raise awareness of the importance of community-based circular economy. While reducing negative impacts on the environment, the sociopreneurship model can boost the community's economy. Bank Sampah Anggrek has the potential to develop into a centre for sustainable waste management innovation at the neighbourhood level by strengthening local capacity and opening up opportunities for cross-sector collaboration.